Relationship Quality Among Older Cohabitors: A Comparison to Remarrieds - Wright, Matthew R (The journals of gerontology. Series B, Psychological sciences and social sciences, 2020)
Later life marital patterns have undergone shifts over the past few decades, including a rapid growth of cohabiting unions. Despite the increase in older adult cohabitation, research on this population has been slow to keep up. Intimate relationships are linked to well-being and relationship quality is especially important because high-quality relationships offer a number of benefits for well-being, whereas poor-quality relationships often are detrimental. This study compares cohabiting and remarried individuals on two measures of relationship quality. Using data from the 2010 and 2012 Health and Retirement Study, I investigate the positive and negative relationship quality of cohabitors relative to their remarried counterparts and whether the association of union type and relationship quality varies by race. Across both positive and negative relationship quality, I found few differences between cohabiting and remarried individuals. Black cohabitors report higher positive relationship quality than remarrieds, whereas White cohabitors and remarrieds do not differ. These findings suggest that cohabiting unions and remarriages are comparable among White older adults, but that Black cohabitors may gain more in terms of positive relationship quality than their remarried counterparts.